Qualitative Researches and Realization of the Project Approach in an Institution of Early Education - Slunjski, Edita (Array, 2012)
The advantages of the project approach in forming the educational process of an institution of early education are considered in the work. The value of the project approach is particularly emphasized, which is based on ideas of constructivism and socio-constructivism, multiple intelligences and different expressive modalities of a child and similar. For realization of the project understood in such a way, it is necessary to provide adequate «learning infrastructures» in the very essence of the educational process, which are related to the research forms of the educator’s professional development. The educator's training for the implementation of qualitative researches, particularly ethnographic and action researches, is considered as a possible tool of improvement of quality of the educational process and as an assumption of realization of the project. One action research is demonstrated in the work, which has been implemented in three institutions of early education as well as the results obtained accordingly. It has been turned out that improvement of quality of the environment for teaching children, redirecting the educator's role from the practice of direct teaching to encouraging discussions among children, providing the educator's indirect support in the process of teaching children, development of the educator's research and reflexive competences, achieving the educators' joint responsibility for children, the space and the whole educational process and establishing the collaborating relations of professional workers of an institution of early education for joint consideration and reflection of the educational process are favourable to development of the project in an institution of early education.